Mutations in regulatory subunit type 1A of cyclic adenosine 5'-monophosphate-dependent protein kinase (PRKAR1A): phenotype analysis in 353 patients and 80 different genotypes - Bertherat, Jérôme; Horvath, Anélia; Groussin, Lionel; Grabar, Sophie; Boikos, Sosipatros; Cazabat, Laure; Libe, Rosella; René-Corail, Fernande; Stergiopoulos, Sotirios; Bourdeau, Isabelle; Bei, Thalia; Clauser, Eric; et al. (The journal of clinical endocrinology and metabolism, 2009)
The "complex of myxomas, spotty skin pigmentation, and endocrine overactivity," or "Carney complex" (CNC), is caused by inactivating mutations of the regulatory subunit type 1A of the cAMP-dependent protein kinase (PRKAR1A) gene and as yet unknown defect(s) in other gene(s). Delineation of a genotype-phenotype correlation for CNC patients is essential for understanding PRKAR1A function and providing counseling and preventive care. A transatlantic consortium studied the molecular genotype and clinical phenotype of 353 patients (221 females and 132 males, age 34 +/- 19 yr) who carried a germline PRKAR1A mutation or were diagnosed with CNC and/or primary pigmented nodular adrenocortical disease. A total of 258 patients (73%) carried 80 different PRKAR1A mutations; 114 (62%) of the index cases had a PRKAR1A mutation. Most PRKAR1A mutations (82%) led to lack of detectable mutant protein (nonexpressed mutations) because of nonsense mRNA mediated decay. Patients with a PRKAR1A mutation were more likely to have pigmented skin lesions, myxomas, and thyroid and gonadal tumors; they also presented earlier with these tumors. Primary pigmented nodular adrenocortical disease occurred earlier, was more frequent in females, and was the only manifestation of CNC with a gender predilection. Mutations located in exons were more often associated with acromegaly, myxomas, lentigines, and schwannomas, whereas the frequent c.491-492delTG mutation was commonly associated with lentigines, cardiac myxomas, and thyroid tumors. Overall, nonexpressed PRKAR1A mutations were associated with less severe disease. CNC is genetically and clinically heterogeneous. Certain tumors are more frequent, with specific mutations providing some genotype-phenotype correlation for PRKAR1A mutations.